New Jersey's Environments : Past, Present, and Future - Maher, Neil M., 1964- (Book collections on Project MUSE., 2006)
Americans often think of New Jersey as an environmental nightmare. As seen from its infamous turnpike, which is how many travelers experience the Garden State, it is difficult not to be troubled by the wealth of industrial plants, belching smokestacks, and hills upon hills of landfills. Yet those living and working in New Jersey often experience a very different environment. Despite its dense population and urban growth, two-thirds of the state remains covered in farmland and forest, and New Jersey has a larger percentage of land dedicated to state parks and forestland than the av.